Structural Reforms and Macroeconomic Performance : Country Cases. (Policy Papers; Policy Paper ;, 2015)
As a companion piece to the Board paper on Structural Reforms and Macroeconomic Performance: Initial Considerations for the Fund, this paper presents a selection of case studies on the structural reform experiences of member countries. These papers update the Board on work since the Triennial Surveillance Review toward strengthening the Fund's capacity to analyze and, where relevant, offer policy advice on macro-relevant structural issues. The paper builds on the already considerable analytical work underway across the Fund, setting out considerations to support a more strategic approach going forward.